Recombinant L. lactis vaccine LL-plSAM-WAE targeting four virulence factors provides mucosal immunity against H. pylori infection - Furui Zhang; Linhan Ni; Zhen Zhang; Xuegang Luo; Xuequan Wang; Wenmiao Zhou; Jiale Chen; Jing Liu; Yuliang Qu; Kunmei Liu; Le Guo (Microbial Cell Factories, 2024)
Abstract Background Helicobacter pylori (H. pylori) causes chronic gastric disease. An efficient oral vaccine would be mucosa-targeted and offer defense against colonization of invasive infection in the digestive system. Proteolytic enzymes and acidic environment in the gastrointestinal tract (GT) can, however, reduce the effectiveness of oral vaccinations. For the creation of an edible vaccine, L. lactis has been proposed as a means of delivering vaccine antigens. Results We developed a plSAM (pNZ8148-SAM) that expresses a multiepitope vaccine antigen SAM-WAE containing Urease, HpaA, HSP60, and NAP extracellularly (named LL-plSAM-WAE) to increase the efficacy of oral vaccinations. We then investigated the immunogenicity of LL-plSAM-WAE in Balb/c mice. Mice that received LL-plSAM-WAE or SAM-WAE with adjuvant showed increased levels of antibodies against H. pylori, including IgG and sIgA, and resulted in significant reductions in H. pylori colonization. Furthermore, we show that SAM-WAE and LL-plSAM-WAE improved the capacity to target the vaccine to M cells. Conclusions These findings suggest that recombinant L. lactis could be a promising oral mucosa vaccination for preventing H. pylori infection.